OPTIMIZATION OF IMPORTED SOYBEAN SUPPLIER SELECTION USING AHP AND SWOT METHODS - eki (Journal Knowledge Industrial Engineering (JKIE), 2023)
OPTIMIZATION OF IMPORTED SOYBEAN SUPPLIER SELECTION USING AHP AND SWOT METHODS